Single nucleotide and copy number polymorphisms of the SULT1A1 gene in a South African Tswana population group - Hlengiwe Mbongwa; Petrus Pretorius; Annemarie Kruger; Gerhard Koekemoer; Carolus Reinecke (South African Journal of Science)
Previous studies on gene mapping have firmly established variation in segments of the DNA structure amongst different population groups. SULT1A1 is one of four SULT1A genes that maps to the short arm of chromosome 16, and this area has been shown to contain many repetitive sequences and to be highly duplicated. Using the polymerase chain reaction (PCR)-based restriction fragment length polymorphism method, we set out to determine the SULT1A1 genotype and allele frequency distributions in the largest sample studied to date: a homogeneous South African Tswana population of 1867 individuals from the Prospective Urban and Rural Epidemiological (PURE) study, and found the SULT1A1*1 and SULT1A1*2 alleles present at a frequency of 0.68 and 0.32, respectively. This finding corresponded with those obtained for the Black, Caucasian, and mixed-race South African groups reported in previous studies. Next, using a quantitative multiplex PCR method to estimate the SULT1A1 gene number of copies in 459 subjects of our population, we discovered between one and five copies: 0.65% of the subjects had a single copy (allele deletion) and 60.14% of the subjects had three or more copies. Our findings correspond with an earlier study on a small African-American group, but differ from those based on two Caucasian groups. Whereas the genotype distribution was comparable to the Caucasian groups, there was a significant difference in the number of copies, which indicated a genetic link between Tswana and African-American populations despite differences in cultural lifestyle associated with their geographical location.